Ink and bone eaudiobook - Caine, Rachel (The Great Library, 2015)
In an exhilarating new series, New York Times bestselling author Rachel Caine rewrites history, creating a dangerous world where the Great Library of Alexandria has survived the test of time ... Ruthless and supremely powerful, the Great Library is now a presence in every major city, governing the flow of knowledge to the masses. Alchemy allows the Library to deliver the content of the greatest works of history instantly-but the personal ownership of books is expressly forbidden. Jess Brightwell believes in the value of the Library, but the majority of his knowledge comes from illegal books obtained by his family, who are involved in the thriving black market. Jess has been sent to be his family's spy, but his loyalties are tested in the final months of his training to enter the Library's service. When he inadvertently commits heresy by creating a device that could change the world, Jess discovers that those who control the Great Library believe that knowledge is more valuable than any human life-and soon both heretics and books will burn ...